A mixed anhydride approach to the preparation of sulfinate esters and allylic sulfones: Trimethylacetic p-toluenesulfinic anhydride. Issue 31 (2nd August 2017) - Jacobsen, Eric; Chavda, Mihir K.; Zikpi, Kokou M.; Waggoner, Stephanie L.; Passini, Daniel J.; Wolfe, Jesse A.; Larson, Robert; Beckley, Chelsea; Hamaker, Christopher G.; Hitchcock, Shawn R.
Graphical abstract: Highlights: A new putative reagent tirmethylacetic p -toluenesulfinic anhydride has been prepared. The reagent has been used to synthesize sulfinate esters. Sulfones were prepared from Baylis-Hillman derived alcohols. The reagent has been used to prepare a N - p -toluenesulfinylamide. Abstract: A reagent combination of toluenesulfinic acid and trimethylacetyl chloride affords a putative trimethylacetic p -toluenesulfinic anhydride. This reagent has been used to prepare a series of sulfinate esters from primary and secondary alcohols. In addition, the reagent was used to convert Baylis-Hillman substrates into allylic sulfones. Attempts to use the reagent to convert amines to sulfinamides were unsuccessful. In contrast, the use of 2-pyrrolidinone afforded N - p -toluenesulfinyl pyrrolidinone in 64% yield. The use of a chiral 4-benzyl-1, 3-oxazolidinone or 4-benzyl-1, 3-oxazolidine-2-thione led to the isolation of S - p -tolyl p -toluenethiosulfonate.